Biphenyl and xanthone derivatives from the twigs of a Garcinia sp. (Clusiaceae) - Ittipon Siridechakorn (2018)
The genus Garcinia is a well known rich source of bioactive xanthones and benzophenones. Some species of this genus also produce flavonoids and biphenyls as minor constituents. In this study, two new biphenyls, doitungbiphenyls A (1) and B (2), along with two biphenyls, schomburgbiphenyl (3) and nigrolineabiphenyl B (4); and four xanthones, 1,3,6-trihydroxy-8-isoprenyl-7- methoxyxanthone (5), morusignin K (6), 1,5-dihydroxyxanthone (7), and 1,7-dihydroxyxanthone (8), were isolated from the acetone extract of the twigs of a Garcinia sp. Their structures were characterized extensively by 1D and 2D NMR spectroscopy and HR-EI-MS. The cytotoxicity of the two new biphenyls against the oral cavity cancer (KB) and the breast cancer (MCF7) cell lines was also evaluated. © 2014 Phytochemical Society of Europe.